Ingredients of Active Compounds and Anti-Diabetic Test of Water Extract of Lannea coromandelica (Houtt) Merr. On Wistar Rats - Nona Rahmaida Puetri; Rita Marleta Dewi; Sahrul; Yasir; Munawir Annasri (IPB University, 2021)
Leaves of Lannea coromandelica (Houtt.) Merr. is one of the plants found in Aceh. This study aims to determine the effect of giving water extract of Lannea coromandellica (Houtt.) Merr. against STZ-induced blood sugar levels of wistar rats. The experimental study used a sample of 25 male and 15 female Wistar rats. This research is experimental with a sample of 25 male and 15 female of Wistar rats. The treatments were given, namely negative control (aquades), positive control (metformin), 50 mg EALC, 100 mg EALC, and 150 mg EALC. The data obtained will be analyzed by using the Kruskal Wallis test to obtain the effectiveness of the treatment and also a descriptive analysis for the average reduction in blood glucose levels. Macro and histological observations were also carried out on the liver and pancreas. The results obtained from the Kruskal Wallis test results showed that there was no effect of EALC on changes in the decrease in blood glucose levels of wistar rats for 14 days of treatment. Observation of the macro organs showed pancreas had a changes. While the histological observations pancreas and liver showed changes. The results of this study indicate that the effectiveness of EALC is not proven to have an effect, this is presumably because the extract concentration is too small so it is not enough to work optimally. Phytochemical test shows that EALC contains flavonoids, steroids, phenolics, tannins, saponins and alkaloids.